Perempuan agama dan pembangunan. Wacana kritik atas peran dan kepemimpinan wanita - YUSUF, Maftuchah ([Tidak Terdaftar], 2000)
Perempuan agama dan pembangunan. Wacana kritik atas peran dan kepemimpinan i